Microbiological parameters as indicators of soil organic carbon dynamics in relation to different land use management - Llorente, Mireia; Turrión, M Belén (European Journal of Forest Research, 2009)
Labile C fractions: microbial biomass C (MBC), K2SO4 extractable C (CK2SO4 ) and the cumulated mineralized C in 21 days incubation at 28C (C–CO2(21d) ), were compared as land use indicators in a calcareous soil under three different management systems: native Querqus ilex forest (under and outside tree cover), a Pinus halepensis plantation, and cropped land (with cereals). Microbial biomass and activity were found to be low and coincided with high carbonate contents. As indicators of land use, CK2SO4 and C–CO2(21d) showed the same sensitivity as MBC. C–CO2 emissions were measured in an incubation experiment in order to study C mineralization kinetics. The data for cumulative amounts of C–CO2 released showed a good ﬁt (R 2 [0.94) to the ﬁrst-order kinetic model Cm = Co(1 - e -kt ). The kinetic parameters Co and Cok were affected by land use and especially by tree cover. Principal components analysis was applied to the data and the relationship among microbial metabolic quotient (qCO2), labile C pools, and MBC revealed a decrease in efﬁciency of organic substrate utilization with an increase in availability and lability of the organic matter.
Keywords: Calcareous soil; Metabolic quotient; Microbial biomass; Soil respiration

Microbiological parameters as indicators of soil organic carbon dynamics in relation to different land use management - Llorente, Mireia; Turrión, M. Belén (European Journal of Forest Research, 2009)
Labile C fractions: microbial biomass C (MBC), K2SO4 extractable C (CK2SO4 ) and the cumulated mineralized C in 21 days incubation at 28C (C–CO2(21d) ), were compared as land use indicators in a calcareous soil under three different management systems: native Querqus ilex forest (under and outside tree cover), a Pinus halepensis plantation, and cropped land (with cereals). Microbial biomass and activity were found to be low and coincided with high carbonate contents. As indicators of land use, CK2SO4 and C–CO2(21d) showed the same sensitivity as MBC. C–CO2 emissions were measured in an incubation experiment in order to study C mineralization kinetics. The data for cumulative amounts of C–CO2 released showed a good ﬁt (R 2 [0.94) to the ﬁrst-order kinetic model Cm = Co(1 - e -kt ). The kinetic parameters Co and Cok were affected by land use and especially by tree cover. Principal components analysis was applied to the data and the relationship among microbial metabolic quotient (qCO2), labile C pools, and MBC revealed a decrease in efﬁciency of organic substrate utilization with an increase in availability and lability of the organic matter.
Keywords: Calcareous soil; Metabolic quotient; Microbial biomass; Soil respiration